To the theory of plasma waves in pereodic plasma waveguides - Zaginaylov, G.I.; Lapshin, V.I.; Tkachenko, I.V. (Вопросы атомной науки и техники, 2000)
Forbidden bands for plasma waves in periodical plasma waveguides are predicted and correctly studied. It was shown that the periodicity influence over frequencies far from the forbidden bands is neglectfully small even for the comparatively large corrugation depth. At the same time while frequency is approaching to any of forbidden bands periodicity influence over dispersion properties and field distribution increases. A group velocity decreases down to zero on the boundaries of forbidden bands. Plasma wave fields concentrates in small space domains and concentration power increases by approaching to the cut off frequencies. This is caused by higher space harmonics contribution which unlike electromagnetic waves in periodical vacuum waveguides have spatial nature and their calculation is of principle.